Estudio farmacognóstico preliminar del tallo y raíz de la planta moringa oleifera lam. - Bastidas Guerrero, Tania Lorena (2015)
The paper aims to conduct a preliminary pharmacognostic study of stem and root (bark and pulp) of Moringa oleifera Lam plant. cultivated in areas of the Academic Unit of Agricultural Sciences, the Technical University of Machala. To this residual moisture, percent ash and the percentage of soluble substances was determined as quality standards set by WHO, 2011. The results for the first two parameters are within the limits for plant drugs, except ash values for stem extract that were elevated.